Baseline tissue concentrations of metal in aquatic oligochaetes: Field and laboratory approaches. (April 2017) - Méndez-Fernández, Leire; Martinez-Madrid, Maite; Pardo, Isabel; Rodriguez, Pilar
Abstract: Metal tissue residue evaluation in benthic macroinvertebrates is an important component of an integrated approach to ecological risk assessment of metals and metalloids in the Nalón River basin (North Spain), where historic mining activities took place. The purpose of this study was to know the baseline tissue concentration of 7 metals (Cd, Cu, Cr, Hg, Ni, Pb, and Zn) and one metalloid (As) in aquatic oligochaetes, sediment burrower organisms, representative of the collector-gatherer functional feeding group in the macroinvertebrate community. Metal concentration was measured in sediment and field aquatic oligochaetes at several reference (minimally disturbed) sites of the Nalón River basin, selected following Water Framework Directive criteria. Metal tissue residues were measured separately in field microdriles and lumbricids and compared with tissue concentrations measured in the aquatic oligochaete Tubifex tubifex exposed to reference sediments from the Nalón and other Cantabrian River basins in 28-d chronic laboratory bioassays. Metal tissue residues in bioassay organisms attained usually higher levels than in field worms, in special for As, Cu, Hg and Zn, although metal levels were within the same order of magnitude. The baseline values for metals were calculated from 90 th percentile (P90) values in field aquatic oligochaetes (microdriles and lumbricids). The P90 for Hg, As and Zn could efficiently discriminate Toxic and Non-Toxic sites, while baseline values calculated for the other metals deserve further research due either to the low range of values found in the present study, or to the regulation of the metal body concentration, as in the case of Cu. Graphical abstract: Highlights: High levels of As and Hg were measured in reference sediments of the Nalón R. basin. Baseline metal levels in oligochaetes are in the range reported in the literature. Metal tissue residues in field and laboratory oligochaetes are comparable. The use of metal tissue baseline values in biomonitoring is encouraged. Abstract : Differences between field and laboratory metal bioaccumulation in aquatic oligochaetes exposed to the sediments from reference unpolluted sites were low for most metals (2–5 times difference), and up to 10 times higher for Hg in laboratory worms.